The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/397596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Mechanisms Governing Shade Responses in Maize

Abstract: 22Light is one of the most important environmental factors affecting plant growth and 23 development. Plants use shade avoidance and shade tolerance strategies to adjust 24 their growth and development thus increase their success in the competition for 25 incoming light. To investigate the mechanism of shade responses in maize (Zea mays), 26 we examined the anatomical and transcriptional dynamics of the early shade response 27 in seedlings of the B73 inbred line. Transcriptome analysis identified 912 differ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In the field, the effect of HDP is similar to that of shading (i.e., light quantity and quality change and photosynthesis decreases when plants are shaded during vegetative and reproductive stages) (Horvath et al, 2018(Horvath et al, , 2019Ma et al, 2018;Mckenzie-Gopsill et al, 2020;Rajcan et al, 2004;Shi et al, 2019). Our data showed that genes encoding photosynthesis and carbohydrate-related processes were significantly downregulated in the lower leaves under HDP (Supplemental Table S8), indicating that high planting density stress might induce plants to regulate environmental fitness at the cost of repressing the genes encoding photosynthesis-related processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the field, the effect of HDP is similar to that of shading (i.e., light quantity and quality change and photosynthesis decreases when plants are shaded during vegetative and reproductive stages) (Horvath et al, 2018(Horvath et al, , 2019Ma et al, 2018;Mckenzie-Gopsill et al, 2020;Rajcan et al, 2004;Shi et al, 2019). Our data showed that genes encoding photosynthesis and carbohydrate-related processes were significantly downregulated in the lower leaves under HDP (Supplemental Table S8), indicating that high planting density stress might induce plants to regulate environmental fitness at the cost of repressing the genes encoding photosynthesis-related processes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one AsaPIF gene was upregulated and one AsaHY5 gene was downregulated in blanched seedlings (Table S1). Homeobox domain (HD) TFs in maize (Zea mays) may play both negative and positive roles in the regulation of axillary bud development [48]. Notably, we identified eight upregulated and four downregulated genes encoding HD TFs in blanched seedlings relative to green seedlings (Table S9).…”
Section: Growth and Developmental Regulation Of Blanched And Green Ga...mentioning
confidence: 99%
“…Light, shade, and darkness all act as signals to regulate phytohormone levels, signaling pathways and transcription factors expression to affect plant development [39,47,48,50,[82][83][84][85]. However, the mechanism by which light quality affects allicin synthesis remains unclear.…”
Section: Allicin Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation